Seorang Penderita Siliko Tuberkulosis dengan Penyulit Pneumotoraks: [Pneumothorax in a Silico-Tuberculosis Patient: A Case Report] - Winariani Koesoemoprodjo; Vinodini Merinda (Faculty of Medicine Universitas Airlangga, 2016)
Background: Silicosis is a lung disease caused by the work because of respirable crystalline silica. Often occurs in workers mining gold, iron, tin, granite, sandstone, slate, foundries, cement, ceramics and glass. The risk of silicosis develop into lung tuberculosis (TB) is higher than patients without silicosis. Another complication of silicosis is secondary spontaneous pneumothorax. Case : A man, 45 years old with a history of work as a bricklayer for 5 years with complaints shortness of breath since three days before admitted to the hospital, chest pain in the right hemithorax, and had chronic cough. Patients is on ATD therapy. From radiographic there is collapse lung, it was shown collapse line on the right hemithorax, and fibroinfiltrat with multiple cavities on both hemithorax. Patients then got chest tube insertion and evaluation for 3 weeks, but the lung has not expanded. From thoracoscopy, there is fibrotic band on the pleural space with conclution right trapped lung. From forcep biopsy on visceral pleura showed a widened alveolar epithelial layer coated with a pile of inflammatory lymphocytes and dust pigments. From broncoscopy, there is chronic lung inflamation. Spectrophotometric analysis from BAL specimens results showed a silica content of 4.25 ppm SiO2 from left BAL an 14.34 ppm SiO2 on the right BAL. Furthurmore, this patient got pleurodesis using betadine agent and continue the ATD. Evaluation the lung is fully expanded. Conclusion : This case illustrates the secondary spontaneous pneumothorax as a complication of silicotuberkulosis. No drug has proven effective for silicosis. Treatment is aimed to the disease complications that occur, in this case is secondary spontaneous pneumothorax and lung TB. Prevention at workplaces that have a risk of silicosis is very important.